Pengembangan Perpustakaan Ramah Disabilitas di Sekolah Luar Biasa Negeri 1 Buleleng - Astiti Maharani (ACARYA PUSTAKA, 2024)
This study aims to determine how to develop a disability-friendly library at the State Special School Library 1 Buleleng. In this study, the researcher used a descriptive research type with a qualitative approach, data collection was carried out using observation techniques, interviews, and document studies related to the research problem. The results of the study obtained that the State Special School Library 1 Buleleng needs to develop a disability-friendly library. This can be seen through a SWOT analysis, which stands for Strengths, Weaknesses, Opportunities, and Threats. The results of this analysis can be used as a reference and evaluation material in developing a disability-friendly library at the State Special School Library 1 Buleleng.